Equatorial E region electric fields at the dip equator: 2. Seasonal variabilities and effects over Brazil due to the secular variation of the magnetic equator - Moro, J. (2016)
In this work, the seasonal dependency of the E region electric field (EEF) at the dip equator is examined. The eastward zonal (Ey) and the daytime vertical (Ez) electric fields are responsible for the overall phenomenology of the equatorial and low‐latitude ionosphere, including the equatorial electrojet (EEJ) and its plasma instability. The electric field components are studied based on long‐term backscatter radars soundings (348 days for both systems) collected during geomagnetic quiet days (Kp ≤ 3+), from 2001 to 2010, at the São Luís Space Observatory (SLZ), Brazil (2.33°S, 44.20°W), and at the Jicamarca Radio Observatory (JRO), Peru (11.95°S, 76.87°W). Among the results, we observe, for the first time, a seasonal difference between the EEF in these two sectors in South America based on coherent radar measurements. The EEF is more intense in summer at SLZ, in equinox at JRO, and has been highly variable with season in the Brazilian sector compared to the Peruvian sector. In addition, the secular variation on the geomagnetic field and its effect on the EEJ over Brazil resulted that as much farther away is the magnetic equator from SLZ, later more the EEJ is observed (10 h LT) and sooner it ends (16 h LT). Moreover, the time interval of type II occurrence decreased significantly after the year 2004, which is a clear indication that SLZ is no longer an equatorial station due to the secular variation of the geomagnetic field.